Detection of the small oligonucleotide products of nucleotide excision repair in UVB-irradiated human skin - Choi, Jun-Hyuk (DNA Repair (Amst), 2019)
UVB radiation results in the formation of potentially mutagenic photoproducts in the DNA of epidermal skin cells. In vitro approaches have demonstrated that the nucleotide excision repair (NER) machinery removes UV photoproducts from DNA in the form of small (~30-nt-long), excised, damage-containing DNA oligonucleotides (sedDNAs). Though this process presumably takes place in human skin exposed to UVB radiation, sedDNAs have not previously been detected in human skin. Using surgically discarded human skin, we have optimized the detection of the sedDNA products of NER from small amounts of human epidermal tissue ex vivo within minutes of UVB exposure and after UVB doses that normally lead to minimal erythema. Moreover, sedDNA generation was inhibited by treatment of skin explants with spironolactone, which depletes the epidermis of the essential NER protein XPB to mimic the skin of xeroderma pigmentosum patients. Time course experiments revealed that a partially degraded from of the sedDNAs could be readily detected even 12 hours following UVB exposure, which indicates that these repair products are relatively stable in human skin epidermis. Together, these data suggest that sedDNA detection may be a useful assay for determining how genetic, environmental, and other factors influence NER activity in human skin epidermis and whether abnormal sedDNA processing contributes to photosensitive skin disorders.